ANALISIS PEMANFAATAN TUTORIAL ONLINE MATA KULIAH WRITING 1 - Afriani Afriani (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2007)
Distance university has a such unique characteristic that differentiates it with the conventional one. Universitas Terbuka (UT) is one of distance education institutions in the world. As a distance university, UT does not employs face to face learning but provides delivery of learning materials through various learning support. This research focuses on the optimal usage of Writing 1 tutorial online by UT’s students. The aims of this research are to asses the quality of Writing 1 tutorial online’s material, difficulty level of Writing 1 tutorial online’s tasks, and the students’ problems in accessing Writing 1 tutorial online. Data were collected from the students who have been registered in Writing 1 tutorial online in two semesters in 2006 registration period and from expert in tutorial online. All 12 registered students were served as samples. They consist of active and passive students who access Writing 1 tutorial online. Data are collected through questionaire sent to the students. The findings reveal that the quality of Writing 1 tutorial online’s material is relatively good, it has been well organized and presented, the students find it easy to do the tasks given in Writing 1 tutorial online, and 75% of samples did not have problem in accessing the tutorial but the rest said they got difficulty in login in